2021
DOI: 10.21037/tlcr-20-958
|View full text |Cite
|
Sign up to set email alerts
|

KRASG12C/TP53 co-mutations identify long-term responders to first line palliative treatment with pembrolizumab monotherapy in PD-L1 high (≥50%) lung adenocarcinoma

Abstract: Background: Pembrolizumab is a standard of care as first line palliative therapy in PD-L1 overexpressing (≥50%) non-small cell lung cancer (NSCLC). This study aimed at the identification of KRAS and TP53defined mutational subgroups in the PD-L1 high population to distinguish long-term responders from those with limited benefit. Methods: In this retrospective, observational study, patients from 4 certified lung cancer centers in Berlin, Germany, having received pembrolizumab monotherapy as first line palliative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…mutational burden and immune checkpoint inhibitor sensitivity among non-G12C KRAS-mutant subtypes. Early data suggest that the presence of KRAS alleles other than G12C mutations (75), especially in conjunction with a TP53 comutation, may represent a negative predictive biomarkers for anti-PD-1/PD-L1 immune checkpoint inhibitors in patients with NSCLC (76). We expect the coming years in the field of KRAS-mutant NSCLC to be very insightful in particular because of the translation of learnings from the KRAS G12C inhibitor field on combinations and comutations to non-G12C KRAS-mutated cancers.…”
Section: Reviewmentioning
confidence: 99%
“…mutational burden and immune checkpoint inhibitor sensitivity among non-G12C KRAS-mutant subtypes. Early data suggest that the presence of KRAS alleles other than G12C mutations (75), especially in conjunction with a TP53 comutation, may represent a negative predictive biomarkers for anti-PD-1/PD-L1 immune checkpoint inhibitors in patients with NSCLC (76). We expect the coming years in the field of KRAS-mutant NSCLC to be very insightful in particular because of the translation of learnings from the KRAS G12C inhibitor field on combinations and comutations to non-G12C KRAS-mutated cancers.…”
Section: Reviewmentioning
confidence: 99%
“…Finally, results from real-world data published by Frost et al from a multicenter, retrospective study evaluated the efficacy of first-line pembrolizumab in 119 patients with KRAS mutant LuAD with high PD-L1 expression (≥50%). Co-mutations in TP53 were also evaluated, and patients with KRAS G12C/TP53 had significantly higher ORR (100% vs 27.3%; p = 0.003) and longer mPFS (33.3 vs 2.8 months; HR, 0.18; 95% CI: 0.06-0.53; p = 0.002) than tumors with KRAS nonG12C/TP53 mutations (41), suggesting that KRAS G12C present better outcomes to immune-based therapies. Furthermore, Noordhof et al reported another retrospective study that evaluated the outcomes of first-line pembrolizumab in 595 patients with metastatic LuAD and high PD-L1 expression.…”
Section: The Efficacy Of Current Immunotherapies In Lung Cancers With...mentioning
confidence: 99%
“…In this study, the BTG2 was correlated to TP53 and ROS1 mutations, but not EGFR , indicating that BTG2 might be involved in the effect of TP53 - or ROS1 ‐mutations on immune activity, and closely associated with immunity. 44 , 77 , 78 , 84 , 85 …”
Section: Discussionmentioning
confidence: 99%